Real-world safety and effectiveness data of trastuzumab deruxtecan and sacituzumab govitecan in breast cancer: a Hellenic Cooperative Oncology Group study - E. Fountzilas; S. Karageorgopoulou; G. Karakatsoulis; D. Tryfonopoulos; K. Papazisis; A. Koutras; A. Koumarianou; G. Zafeiri; E. Biziota; A. Nikolaidi; I. Boukovinas; E. Vrana; et al. (ESMO Real World Data and Digital Oncology)
Background: The study aimed to evaluate real-world effectiveness and toxicity data of trastuzumab deruxtecan (T-DXd) and sacituzumab govitecan (SG) in pretreated patients with metastatic breast cancer (mBC). Patients and methods: A retrospective multicenter review of medical records of patients with mBC treated with T-DXd and/or SG at 24 Departments of Oncology, affiliated with the Hellenic Cooperative Oncology Group (HeCOG) was carried out. Patients with triple-negative BC (TNBC), HER2-positive, and/or hormone receptor (HR)-positive mBC who received at least one cycle of T-DXd and/or SG in any line of treatment were included. The primary endpoint was the toxicity rate of each drug. Results: From January 2020 to April 2024, 312 patients received treatment; 226 (72.4%) received T-DXd and 60 (19.2%) SG, while 26 (8.3%) patients received both agents. Adverse events (AEs) were reported in 57.1% of patients treated with T-DXd and 56.6% of patients treated with SG. The most common AEs were nausea (28.1%) and fatigue (22.5%) among patients treated with T-DXd, and fatigue (20.7%) and neutropenia (12.6%) among those treated with SG. Toxicity-related discontinuation was reported in 12 (8.8%) and 2 (3.2%) patients, respectively, who received T-DXd and SG. Interstitial lung disease was observed in 17 (6.9%) patients treated with T-DXd. The 12-month progression-free survival (PFS) rate was 69.6 [interquartile range (IQR) 61.4-79] in patients with HER2-positive and 46.5 (IQR 28.6-46.5) in patients with HER2-low mBC receiving T-DXd. In patients with TNBC receiving SG, the 12-month PFS rate was 16.2 (IQR 8.1-32.4), whereas in patients with HR-positive/HER2-negative mBC, it was 23.6 (IQR 13.8-40.3). Conclusions: Real-world data on the use of T-DXd and SG in patients with mBC provide significant clinical insights into the toxicity and effectiveness of each agent.